Overview of education system for oral hygienists in Taiwan - Ling-Hsia Wang; Feng-Chou Cheng; Wan-Chi Liu; Po-Fang Tsai; Chun-Pin Chiang (Journal of Dental Sciences, 2022)
Background/purpose: Currently, Taiwan has a very complete education system of oral hygiene, but there is still no licensing system for oral hygienists. This study explored mainly the profile of education system for oral hygienists in Taiwan from 2017 to 2021. Materials and methods: This study used the documentary analysis and secondary data analysis to survey mainly the development of oral hygiene education system in Taiwan, and the changes of oral hygiene students and graduates from 2017 to 2021. Results: In Taiwan, currently, there are 8 oral hygiene schools which offer associate, bachelor, and master degrees in oral hygiene. The oral hygiene enrollment quotas determined by the Ministry of Education increased from 343 quotas in 9 programs in 2017 to 500 quotas in 13 programs in 2021, while new oral hygiene students who completed registration increased from 282 students in 2017 to 353 students in 2021. The registration rate of the five-year training program of junior college was significantly higher than the other programs. The number of oral hygiene students with official student status increased from 604 students in 2017 to 1349 students in 2021. The total increase was 745 students from 2017 to 2021 with a total increase rate of 123.34%. Conclusion: In Taiwan, although the manpower of oral hygienists is important for public oral health, they usually work as dental assistants or change their careers. It is imperative to continue to promote the certification system for oral hygienists to improve the professionalism of this occupation.